Palatability Test of Mineral Herbal Blocks on Performans of Local Sheep - Nurmi, Aisyah; Harahap, Muharram Fajrin (Talenta Publisher, 2019)
This research was aimed to study of palatability and body weight gain local sheeps given minerals herbal (MBH). The farms used in this study were male 4 local sheep at the age of 12-18 months who showed symptoms of mineral deficiency. The research method used is the Latin Square Design (LSD). The treatment given is: H0 = Basal Feed + Salt; H1 = Basal Feed + Salt + Mineral + Turmeric; H2 = Basal Feed + Salt + Mineral + Ginger; H3 = Basal Feed + Salt + Mineral + Turmeric + Ginger. The research parameter is the mineral palatability of herbal blocks and body weight gain. The results showed that MBH given turmeric (10%), ginger (10%) and a combination of 5% + 5% ginger showed a non-significant effect on feed consumption and conversion. Palatability test showed that all MBH treatments were favored by local sheep, but the highest palatability of MBH was by adding ginger; followed by a combination of ginger and turmeric; and the lowest palatability is turmeric. Based on palatability tests, MBH with turmeric supplementation of 10%; 10% ginger or a combination of 5% ginger + 5% turmeric in the form of Herbal Minerals Block has a good palatability (preferred) and can improve the performance of local sheep.